Nelson handwriting developing skills book 1 - Jackman, John; Warwick, Anita (Oxford University Press UK, 2014)
The Developing Skills Books provide the structured progression throughout the course. Each double page spread opens with a Focus in which the main point of the lesson is clearly stated; this is then followed by Extra and Extension activities of increasing difficulty. Throughout the books pupils are encouraged to think about the writing process and assess their own work.